Smart Albumin-Biomineralized Nanocomposites for Multimodal Imaging and Photothermal Tumor Ablation - Wang, Yong (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.